Regulation of cyclin D-dependent kinase 4 (cdk4) by cdk4-activating kinase. - Kato, J Y (1994)
The accumulation of assembled holoenzymes composed of regulatory D-type cyclins and their catalytic partner, cyclin-dependent kinase 4 (cdk4), is rate limiting for progression through the G1 phase of the cell cycle in mammalian fibroblasts. Both the synthesis and assembly of D-type cyclins and cdk4 depend upon serum stimulation, but even when both subunits are ectopically overproduced, they do not assemble into complexes in serum-deprived cells. When coexpressed from baculoviral vectors in intact Sf9 insect cells, cdk4 assembles with D-type cyclins to form active protein kinases. In contrast, recombinant D-type cyclin and cdk4 subunits produced in insect cells or in bacteria do not assemble as efficiently into functional holoenzymes when combined in vitro but can be activated in the presence of lysates obtained from proliferating mammalian cells. Assembly of cyclin D-cdk4 complexes in coinfected Sf9 cells facilitates phosphorylation of cdk4 on threonine 172 by a cdk-activating kinase (CAK). Assembly can proceed in the absence of this modification, but cdk4 mutants which cannot be phosphorylated by CAK remain catalytically inactive. Therefore, formation of the cyclin D-cdk4 complex and phosphorylation of the bound catalytic subunit are independently regulated, and in addition to the requirement for CAK activity, serum stimulation is required to promote assembly of the complexes in mammalian cells.